2021
DOI: 10.1002/jbt.22827
|View full text |Cite
|
Sign up to set email alerts
|

Azilsartan prevented AGE‐induced inflammatory response and degradation of aggrecan in human chondrocytes through inhibition of Sox4

Abstract: Advanced glycation end products (AGEs)‐induced inflammation and degradation of aggrecan in human chondrocytes play an important role in the progression and development of osteoarthritis (OA). Azilsartan, an angiotensin II receptor antagonist, has been licensed for the treatment of high blood pressure. However, the effects of Azilsartan in OA and AGEs‐induced damages in chondrocytes have not been previously reported. The injured chondrocytes model was established by incubating with 5 μmol/L AGEs. 3‐(4,5‐Dimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Recently, several studies have P r e p r i n t demonstrated the protective benefits of AZL in a wide range of diseases. For example, Liu et al showed that AZL suppressed inflammatory response by increasing e-NOS phosphorylation [9]. Furthermore, it inhibited hydroperoxide-induced oxidative stress in endothelial cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have P r e p r i n t demonstrated the protective benefits of AZL in a wide range of diseases. For example, Liu et al showed that AZL suppressed inflammatory response by increasing e-NOS phosphorylation [9]. Furthermore, it inhibited hydroperoxide-induced oxidative stress in endothelial cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…Azilsartan, a blocker of the AT1R receptor (ARB), has been approved for clinical use, and it inhibits AT1R-mediated biological effects. Azilsartan restores endothelial function in the inflammatory response by suppressing inflammation and increasing e-NOS phosphorylation (Matsumoto et al, 2014;Liu et al, 2016;Lei et al, 2021). Meanwhile, azilsartan inhibits LPS-induced inflammatory responses in macrophages by suppressing oxidative stress (Dong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%